Use of Complementary and Alternative Medicine in Children with Cancer: A Study at a Swiss University Hospital. - Tatjana Magi; Claudia E Kuehni; Loredana Torchetti; Laura Wengenroth; Sonja Lüer; Martin Frei-Erb (PLoS ONE)
Background Though complementary and alternative medicine (CAM) are frequently used by children and adolescents with cancer, there is little information on how and why they use it. This study examined prevalence and methods of CAM, the therapists who applied it, reasons for and against using CAM and its perceived effectiveness. Parent-perceived communication was also evaluated. Parents were asked if medical staff provided information on CAM to patients, if parents reported use of CAM to physicians, and what attitude they thought physicians had toward CAM. Study design All childhood cancer patients treated at the University Children's Hospital Bern between 2002-2011 were retrospectively surveyed about their use of CAM. Results Data was collected from 133 patients (response rate: 52%). Of those, 53% had used CAM (mostly classical homeopathy) and 25% of patients received information about CAM from medical staff. Those diagnosed more recently were more likely to be informed about CAM options. The most frequent reason for choosing CAM was that parents thought it would improve the patient's general condition. The most frequent reason for not using CAM was lack of information. Of those who used CAM, 87% perceived positive effects. Conclusions Since many pediatric oncology patients use CAM, patients' needs should be addressed by open communication between families, treating oncologists and CAM therapists, which will allow parents to make informed and safe choices about using CAM.